Healthcare staff's evaluation of a walk‐in centre at a healthcare centre in an immigrant‐dense area. Issue 9 (8th January 2019) - Wärdig, Rikard; Hadziabdic, Emina; Hjelm, Katarina
Abstract: Aims and objectives: To evaluate a walk‐in centre at a healthcare centre in an immigrant‐dense area where a high proportion of the patients have limited language ability in Swedish, from the perspective of healthcare personnel. Background: Increased global migration results in higher vulnerability in migrants, with the risk of increased morbidity and mortality. Migrants' health often deteriorates, which can be attributed to an increased level of stress and adaptation to a new lifestyle. Therefore, immigrants are at higher risk of being affected by, for example, cardiovascular diseases and diabetes. This requires access to good health care. Design: A qualitative exploratory study was conducted, using semi‐structured interviews. Content analysis was used in the analysis process. Methods: Semi‐structured interviews were held with 15 purposively sampled doctors and nurses, working at a healthcare centre in Sweden. Data were collected during autumn 2017. The study was performed in accordance with COREQ. Results: Working at the walk‐in centre involved caring for everything from basic to advanced health problems and meant a high pace that required stress‐resistant personnel. The walk‐in centre was described as both promoting and threatening patient safety. The personnel had several ideas on how to develop the walk‐in centre. Conclusions: A walk‐in centre can be seen as a necessity related to issues of ensuring patient safety and delivering care for everyone in an immigrant‐dense area. However, it cannot be the only form of care offered, as it seems not be adapted to certain groups, such as people with disabilities and the elderly. Relevance to clinical practice: The findings emphasise that a walk‐in centre is a way to increase accessibility for the entire population and offer equal care for all, even if it involves challenges that need to be addressed.